Harnessing Evolutionary Toxins for Signaling: Reactive Oxygen Species, Nitric Oxide and Hydrogen Sulfide in Plant Cell Regulation - Hancock, John T. (Frontiers in Plant Science, 2017)
During the early periods of evolution, as well as in niche environments today, organisms have had to learn to tolerate the presence of many reactive compounds, such as reactive oxygen species (ROS), nitric oxide (NO) and hydrogen sulfide (H2S). It is now known that such compounds are instrumental in the signalling processes in plant cells. There are enzymes which can make them, while downstream of their signalling pathways are coming to light. These include the production of cGMP, the activation of MAP kinases and transcription factors, and the modification of thiol groups on many proteins. However, organisms have also had to tolerate other reactive compounds such as ammonia, methane and hydrogen gas, and these too are being found to have profound effects on signalling in cells. Before a holistic view of how such signalling works, the full effects and interactions of all such reactive compounds needs to be embraced. A full understanding will be beneficial to both agriculture and future therapeutic strategies.